A five-membered lactone prodrug of CBI-based analogs of the duocarmycins. Issue 23 (3rd June 2015) - Uematsu, Mika; Brody, Daniel M.; Boger, Dale L.
Graphical abstract: Abstract: The preparation, characterization, and examination of the CBI-based 5-membered lactone5 capable of serving as a prodrug or protein (antibody) conjugation reagent are disclosed along with its incorporation into the corresponding CC-1065 and duocarmycin analog6, and the establishment of their properties.